Experiences of using the internet among people with aphasia : challenges and opportunities - Henriksson, Ingrid; Johansson-Malmeling, Charlotte; Gustavsson, Catharina; Johansson, Stefan (Aphasiology, 2025)
“Digital participation” refers to being actively involved in the digital society and using information and communication technology, above all the internet. However, not everyone has access to this global network and the ability to use it. The aim of the study was to explore experiences of using the internet and digital participation among people with aphasia (PWA) in Sweden by analysing data from an online survey undertaken in 2021. Methods & Procedures: The study has a descriptive design using mixed methods. Sixty-four participants with self-reported aphasia and a reference group of 1116 members of the general public answered the same survey with questions related to internet use and the digital society. Answers from both groups to ten multiple-choice questions were analysed statistically, and the PWA’s answers to eleven open-ended questions were analysed using reflexive thematic analysis. Outcomes & Results: Quantitatively, the analysis showed that answers concerning internet use differed statistically significantly between the two groups. Qualitatively, the analysis identified two themes: “The internet imposes heavy demands” and “The internet provides opportunities”, with various sub-themes. Conclusions: PWA described how the internet is very demanding. However, they also reported positive experiences and confidence in the potential of the technology. Even so, the internet can be exclusionary, and it is important to ensure that facilitating factors are considered in the development of technology and technology-mediated communication, so that communication opportunities for PWA and others will be enhanced.
Keywords: accessibility; Aphasia; digital inclusion; internet